Effect of Topical Antiinflammatory Drugs on Mechanical Behavior of Rabbit Cornea. Issue 2 (April 2017) - Lepore, Domenico; De Santis, Roberto; Pagliara, Monica M.; Gloria, Antonio; Oliviero, Olimpia; Nucci, Carlo; Improta, Giovanni; Triassi, Maria; Ambrosio, Luigi
Background: A variety of antiinflammatory therapies are employed to promote corneal wound healing. The effects of steroidal and nonsteroidal antiinflammatory drugs on the biomechanical properties of rabbit cornea were investigated over time using tensile tests. Methods: Full-thickness incisions were made and used to analyze the effects of dexamethasone sodium phosphate 0.1% and diclofenac sodium 0.1% on corneal biomechanical properties during wound healing at 7, 14 and 21 days after surgery. Results: The full-thickness incision deeply modified all of the mechanical properties. At 3 weeks after incision, regardless of the drug therapy, the tensile modulus was about 70% of the value for the intact cornea. Conclusions: Topical treatment with dexamethasone was particularly effective during the first week after surgery; the second week after surgery, a similar result was observed in the corneas treated with diclofenac. Low doses of steroidal and nonsteroidal antiinflammatory drugs would seem to have the potential to improve biomechanical properties only during the early stage of the healing process of the cornea.